Examining the critical success factors influencing the diffusion of AI in tax administration in Botswana - Edmore Munjeyi; Danie Schutte (Cogent Social Sciences, 2024)
The assimilation of AI in the domain of tax can (re)solve the recurring and pervasive challenges of tax fraud, tax evasion, tax avoidance, and all other forms of tax noncompliance. However, the literature on AI adoption in the domain of tax is still fragmented, meaning that little is known about the most momentous CSFs influencing AI adoption in taxation. Thus, this study makes a groundbreaking attempt by examining the key factors (CSFs) affecting AI assimilation in tax administration in Botswana. This study uses the TOE paradigm to establish significant CSFs for AI deployment in the context of the Botswana tax system. Using a qualitative research approach, this study found nine (9) constructs including compatibility, complexity, relative advantage, leadership vision, top management support, adequate resources, government, regulatory support, and time as key factors or primary drivers (CSFs) of AI adoption in tax administration in Botswana. The results of this study are valuable for AI system developers, tax practitioners (or experts), and policymakers in formulating (or designing) policies to facilitate the successful diffusion of AI in tax administration.